Degradation of switchgrass by Bacillus subtilis 1AJ3 and expression of a beta-glycoside hydrolase - Ma, Lingling; Wang, Xin; Zhou, Jingwen; Lü, Xin (Frontiers in Microbiology, 2022)
Increasing demand for carbon neutrality has led to the development of new techniques and modes of low carbon production. The utilization of microbiology to convert low-cost renewable resources into more valuable chemicals is particularly important. Here, we investigated the ability of a cellulolytic bacterium, Bacillus subtilis 1AJ3, in switchgrass lignocellulose degradation. After 5 days of culture with the strain under 37°C, cellulose, xylan, and acid-insoluble lignin degradation rates were 16.13%, 14.24%, and 13.91%, respectively. Gas chromatography-mass spectrometry (GC-MS) analysis and field emission scanning electron microscopy (FE-SEM) indicated that the lignin and surface of switchgrass were degraded after incubation with the bacterial strain. Strain 1AJ3 can grow well below 60°C, which satisfies the optimum temperature (50°C) condition of most cellulases; subsequent results emphasize that acid-heat incubation conditions increase the reducing sugar content in a wide range of cellulosic biomass degraded by B. subtilis 1AJ3. To obtain more reducing sugars, we focused on β-glycoside hydrolase, which plays an important role in last steps of cellulose degradation to oligosaccharides. A β-glycoside hydrolase (Bgl-16A) was characterized by cloning and expression in E. coli BL21, and further determined belong to glycoside hydrolase (GH) 16 family. The Bgl-16A had an enzymatic activity of 365.29 ± 10.43 U/mg, and the enzyme’s mode of action was explained by molecular docking. Moreover, the critical influence on temperature (50℃) of Bgl-16A also explained the high-efficiency degradation of biomass by strain under acid-heat conditions. In terms of potential applications, both the strain and the recombinant enzyme showed that coffee grounds would be a suitable and valuable substrate. This study provides new understanding of cellulose degradation by B. subtilis 1AJ3, that both the enzyme action mode and optimum temperature limitation by cellulases could impact the degradation. It also gave new sight to unique advantages utilization in the industrial production of green manufacturing.